Harry Potter around the UK - Dugan, Mary Katherine (Qualitative and Quantitative Methods in Libraries, 2019)
This study examines scholarly literature and documents sites and collections in the United Kingdom related to the Harry Potter book and movie series and the author J.K. Rowling.